Auditory Temporal Processing Skills in Dancers and Non Dancers - Pisharody, Indira C; Magudilu Srishyla Kumar Lakshmi; Supritha Aithal (Journal of All India Institute of Speech and Hearing)
Perception of temporal aspects of sound is crucial for discrimination, identi cation, and comprehension of speech, particularly in noisy backgrounds. Studies have shown superior temporal processing abilities in musicians compared to non-musicians attributable to their musical training. Dance is another form of art where body movements are chore- ographed to music necessitating active listening to the temporal aspects of music (tala and laya) in order to express them through movements. Considering that it involves similar task as in musicians the study explored trained dancers’ auditory temporal processing abilities. Ten professional dancers and 10 non-dancers with mean age 24 and 22 years respectively, participated in the study. Gap detection threshold (GDT) and Temporal modulation transfer function (TMTF) were obtained toassess their temporal processing abilities. Comparison of mean scores of GDT and TMTF between the two groups revealed lower mean thresholds in GDT (2.42 vs. 2.66), and TMTF (at 16, 32, 64, 128 Hz) thresholds in dancers. MANOVA revealed signi cant di erence in scores of TMTF (at 16, 32, 64 & 128 Hz). Based on these ndings, it was concluded that dancers have better temporal processing compared to non-dancers owing to the training they undergo.